O kreacjach bohaterek "Ballad i romansów" Adama Mickiewicza. Próba lektury feministycznej = Heroines' creations in "Ballades and Romances" by Adam Mickiewicz. An attempt of a feminist reading - Rawski, Jakub (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article attempts to answer the questions: does the artistic creation of heroines "Ballades and Romances" by Adam Mickiewicz bear the hallmarks of stereotypical patriarchal optics or does it go beyond the limits of male worldview and a man in general? To what extent, how, and if actually indeed the author of "Sir Thaddeus" contained in his poetic cycle signs of emancipation sensibility? Are the heroines of ballades women liberated from sex constraints imposed by culture? The purpose of this contribution is also an attempt to make an "updating reading" of a significant nineteenth century text; showing it in contemporary perspective, but particularly emphasizing the core of romantic anthropology which was "inner man" with the mystical dialectic of what was external and what was internal.
Keywords: Mickiewicz, Adam (1798-1855); ballada; feminizm; emancypacja; stereotypy; feminism; ballade; stereotypes